Policy bias and agriculture: partial and general equilibrium measures - Bautista, Romeo M.; Robinson, Sherman; Tarp, Finn; Wobst, Peter (Wiley, 2001)
The paper examines the impact of industrial protection, agricultural export taxes, and overvaluation of the exchange rate on the balance between the agricultural and nonagricultural sectors. Various agricultural terms-of-trade indices are constructed to measure the policy bias against agriculture in a computable general equilibrium (CGE) framework and compare the results with earlier partial equilibrium measures. Our results indicate that the partial equilibrium measures miss much of the action operating through indirect product and factor market linkages, while overstating the strength of the linkages between changes in the exchange rate and prices of traded goods on the agricultural terms of trade.